2011
DOI: 10.1177/0040517511420753
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic performance of p-aramid fabrics impregnated with shear thickening fluid; Part I – Effect of laminating sequence

Abstract: The objective of this research was to characterize the ballistic performance of p-aramid fabrics impregnated with shear thickening fluid (STF) focusing on the laminating sequence of the layers. A panel of all neat Kevlar fabrics and two hybrid panels of neat and STF impregnated Kevlar fabrics were tested against 9 mm bullets at 436 m/s for body armor application. When the STF impregnated fabrics were laminated behind the neat Kevlar layers (N/S-panel), the backface signature decreased compared to the panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…The failure of the STF impregnated structure is by rupture of fibres and yarns rather than their slippage. Some other studies showed that the enhancement of impact resistance was due to higher inter-yarn friction in the fabric brought by STF with constraining the pull-out of yarns [18,[21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…The failure of the STF impregnated structure is by rupture of fibres and yarns rather than their slippage. Some other studies showed that the enhancement of impact resistance was due to higher inter-yarn friction in the fabric brought by STF with constraining the pull-out of yarns [18,[21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…e technology of AuTx has a large potential for development [1]. Nowadays the high interest for goods produced from aramide bres and fabrics has been proved by numerous research [2][3][4][5][6][7][8]. In this paper we examined the impregnation processes of high performance fabrics made from aramid bres designed for the manufacturing of athletic sportswear for extreme sports using the neural network mapping technique when searching for optimal conditions regarding the studied process.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that the ballistic and stab performance of materials can be enhanced when impregnated with shear thickening fluid (STF) [2][3][4]. Since the shear thickening phenomenon is a non-Newtonian behavior widely observed in concentrated colloidal suspensions, STF is prepared by making the colloidal suspension of solid particles in a liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, dense suspensions show more shear thickening effects. The dispersed colloidal particles form clusters, often denoted by the term 'hydroclusters' [3], leading to increased viscosity (i.e., shear thickening). Most previous studies on STF-treated fabrics have been focused on STF containing spherical silica particles because the suspension of silica particle in poly (ethylene glycol) (PEG) shows discontinuous shear thickening at low volume fraction about 0.5 [4].…”
Section: Introductionmentioning
confidence: 99%